Diffusion tensor imaging abnormalities in photosensitive juvenile myoclonic epilepsy. (28th April 2015) - von Podewils, F.; Runge, U.; Krüger, S.; Geithner, J.; Wang, Z. I.; Khaw, A. V.; Angermaier, A.; Gaida, B.; Domin, M.; Kessler, C.; Langner, S.
<x xml:space="preserve">Abstract</x> Background and purpose Multiple structural white matter abnormalities have been described in patients with juvenile myoclonic epilepsy (JME). In the present study, the question of whether microstructural variations exist between the two subgroups of JME, with and without photoparoxysmal responses (PPR positive and negative), was addressed using diffusion tensor imaging. Methods A selection of 18 patients (eight PPR positive) from a tertiary epilepsy center diagnosed with JME and 27 healthy controls was studied. The following regions of interest were investigated: the ascending reticular activating system, lateral geniculate nucleus, genu of the internal capsule, ventromedial thalamus and inferior cerebellar peduncle. Results Widespread white matter microstructural abnormalities in JME and in particular in PPR positive cases were identified. PPR positive patients demonstrated increased fractional anisotropy in the ascending reticular activating system and ventromedial thalamus compared to PPR negative patients and healthy controls. Reduced fractional anisotropy of the lateral geniculate nucleus was observed in the entire JME group compared to healthy controls. Conclusions Several microstructural variations between PPR positive and negative JME patients have been identified. Our findings highlight the pivotal role of the thalamus in the pathophysiology of primary generalized seizures and suggest that thalamo‐premotor connections are both an essential part of epileptic networks and important in the pathogenesis of photosensitivity.